The invention of public space : designing for inclusion in Lindsay's New York - Mogilevich, Mariana (Minneapolis University of Minnesota Press, 2020)
"The interplay of psychology, design, and politics in experiments with urban open space"--
Keywords: Public spaces -- History; Public spaces -- Social aspects -- History; City planning -- History